Evaluation of Revenue Accounting System at Pos Indonesia Pulo Brayan Branch using Framework Matrix Approach - Anindya, Desy Astrid; Aisyah, Siti; Anggriani, Dwi Pertiwi; Fadillah, Tri Dessy; Habibie, Muhammad; Risal, Taufiq; Nurhusna, Salsa (LifeSciFi, 2024)
Pos Indonesia Pulo Brayan Branch is a subsidiary or assistant company of PT. Pos Indonesia (Persero) which aims to facilitate serving the community with certain needs at PT. Pos Indonesia (Persero). The purpose of this study is to analyze and determine whether the revenue accounting recording system at the branch office has been running well and effectively. The revenue accounting recording system at the branch office is still ineffective due to problems experienced in the accounting recording system used which is still manual, then due to human resources who are less careful and less qualified in their fields of work. How The branch office carries out the company's revenue accounting recording system is by Every income received by The branch office is recorded manually in the company's cash book on a daily basis in reporting the company's financial statements. So the efforts that should be taken by the branch office is changing the manual recording system to a computerized recording system so that the company's cash financial reports can run effectively, as well as seeking to replace or conduct special training for human resources responsible for their work in order to improve performance in the company.